Social Control of Deviance and Knowledge in Social Work from an Anti-oppressive Perspective. Issue 2 (4th May 2021) - Scarscelli, Daniele
ABSTRACT: This paper will examine the relationship between social control of deviance, ethical principles and social work. I will address this issue by adopting a specific social work theoretical perspective, that of "critical social work". In this article a specific phase of social workers' control of deviance in social work will be examined: the phase in which they collect information through specific fact-finding modalities, in order to decide whether, and in what way, social services will intervene. I chose a specific aspect of social work with involuntary clients to develop my analysis: child protection. I will organize my analysis in two parts. In the first part I will tackle the issue of social control in social work. I will subsequently analyze two theoretical paradigms (Positivism and Constructionism) within which child neglect and abuse are conceptualized and operationalized. In the second part, I will examine a case study, the story of a drug-addicted mother who had one of her children removed, with the aim of highlighting how the paradigm that guides fact-finding activity on a given phenomenon can influence the forms in which social control is exercised, favoring or hindering anti-oppressive practices. The analysis of mother's story shows how the positivist framework applied by the social workers in the decision to remove her child, affected the form in which power and social control was exercised, favoring the transition from protective power to oppressive power. The categorization of clients, aimed at the identification of the risks children run in their family contexts, may reduce social workers' activity to pure control of family life in an "antagonistic role" to their clients.